Hopsca III / J Tart - Tartm J. (China : JTart Publishing Limited, 2013)
HOPSCA (hotel, office, parking, shopping mall, convention, and apartment) is a rising concept for architecture design. With the fast pace of urbanization, we search for an efficient self-sufficient urban model. The projects here make a breakthrough from traditional single-function projects such as commercial places, offices, residences, entertaining places, transportation projects, and so on, to the establishment of organic relationships among them. Here you would find the popular understanding and practice of the burgeoning concept of HOPSCA.
engineering bookfair2015
Keywords: Architecture -- Design; Architecture -- Buildings